Bromination of o-Hydroxyacetophenones and o-Hydroxychalcones with Potassium Bromide-Potassium Bromate - F. Hussain, Kaneez; Vijayvargiya, Deepika; Hussain, S.; Verma, B.L. (Asian Journal of Chemistry, 2010)
Bromination of o-hydroxyacetophenones (I) and 2' -hydroxychalcones (IV) with KBr-KBrO3 in glacial acetic acid medium gave corresponding nuclear substituted 3-bromo-2-hydroxy-acetophenone (II) and 3'-bromo-2'-hydroxychalcone(V) derivatives respectively. However, bromination of 2'-hydroxy- 5'-methylchalcone (IVc) resulted in 8-bromo-6- methylflavanone (VI). All the synthesised compounds have been characterised by elemental analysis and spectral data.